Evaluation of the content of polyphenols, flavonoids, tannins, antioxidant capacity and antibacterial activity of Pelargonium graveolens flower extracts - Najlae, El-otmani; Ikrame , Zeouk; Hayat , Ben-saghroune; Ahmed, Zahidi (Plant Science Today, 2025)
Pelargonium graveolens has garnered attention for its therapeutic properties, especially in treating dermatological conditions. The aim of this study was to investigate the phytochemicals, antioxidant action and antibacterial effect of its flower extracts obtained through maceration, sonication and infusion. The findings show that the highest total phenolic content was obtained from the hydroethanolic sonication extract (280.39 mg GAE/g), followed by the hydroethanolic maceration extracts (272.87 mg GAE/g). The total flavonoid content varied from 21.51 mg EQ/g (hydroethanolic maceration) to 12.32 mg EQ/g (aqueous infusion). Condensed tannins were highest in the hydroethanolic maceration extracts (8.40 mg/mL). Additionally, the antioxidant action was assessed using the DPPH, FRAP, TAC and ABTS methods. The extracts from hydroethanolic sonication showed a high free radical scavenging capacity (IC50 = 0.31 mg/mL) compared with extracts from aqueous infusion and hydroethanolic maceration. However, antibacterial tests revealed that all extracts had better activity against Gram-positive bacteria. The hydroethanolic maceration extracts showed pronounced sensitivity, exhibiting zones of inhibition ranging from 13 to 24 mm for Gram-negative bacteria and 19 to 24 mm for Gram-positive bacteria. These extracts demonstrated significant efficacy against methicillin-resistant Staphylococcus aureus and Panton-Valentine Leukocidin-Positive Staphylococcus aureus. These findings suggest potential applications in the pharmaceutical and dermatological fields, particularly for developing natural antioxidant and antibacterial agents.